Returns and determinants of technical efficiency in small-scale Malabari goat production units in Kerala, India - Rani Alex; Raghavan Kunniyoor Cheemani & Naicy Thomas (Trop Anim Health Prod, 2013)
A stochastic frontier production function was employed to measure technical efficiency and its determinants in smallholder Malabari goat production units in Kerala, India. Data were obtained from 100 goat farmers in northern Kerala, selected using multistage random sampling. The parameters of the stochastic frontier production function were estimated using the maximum likelihood method. Cost and return anal- ysis showed that the major expenditure was feed and fodder, and veterinary expenses were secondary. The chief returns were the sale of live animals, milk and manure. Individual farm technical efficiency ranged from 0.34 to 0.97 with a mean of 0.88. The study found herd size (number of animal units) and centre (locality of farm) significantly affected tech- nical efficiency, but sex of farmer, education, land size and family size did not. Technical efficiency decreased as herd size increased; half the units with five or more adult animals had technical efficiency below 60 %.